Fetal and Infant Growth and the Cardiovascular Stress Response in Adolescence: A Cardiovascular Magnetic Resonance Imaging Study in a Pediatric Population‐Based Cohort - Arwen S. J. Kamphuis; Alexander Hirsch; Dimitris Rizopoulos; Ricardo P. J. Budde; Arno A. W. Roest; Vincent W. V. Jaddoe; Romy Gaillard (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Abnormal birth weight and infant weight gain are recognized as risk factors for cardiovascular diseases. Underlying mechanisms remain unclear. Exercise testing can detect subtle differences in cardiovascular function not present at rest. We examined associations of fetal and infant growth with the cardiovascular stress response in adolescence. Methods We examined a subsample of 207 children from a population‐based prospective cohort from fetal life onwards. Fetal and infant growth were assessed from the second trimester to 2 years. At 16 years, participants performed an isometric handgrip exercise with continuous heart rate and blood pressure monitoring and cardiovascular magnetic resonance imaging. Results Children showed a clear peak in heart rate and systolic and diastolic blood pressure during exercise, followed by a decrease below baseline after exercise cessation, before stabilizing. Higher gestational age was associated with lower systolic blood pressure throughout the exercise (differences per SD score increase in gestational age: rest, −2.24 mm Hg [95% CI, −4.23 to −0.25 mm Hg], peak exercise (−2.37 mm Hg [95% CI, −4.70 to −0.04 mm Hg]), recovery (−2.57 mm Hg [95% CI, −4.72 to −0.42 mm Hg])) but not with heart rate or CMR outcomes. No consistent associations were present for birth weight or infant growth with the cardiovascular stress response. Conclusions A lower gestational age at birth is associated with an altered response to exercise in systolic blood pressure. Fetal or infant growth is not associated with differences in cardiovascular response to exercise‐induced stress in adolescence in a relatively healthy population. Follow‐up of children born preterm is important to enable early identification and prevention of cardiovascular disease development.